NLRP3 Inflammasome Participates in Host Response to Neospora caninum Infection - Wang, Xiaocen; Gong, Pengtao; Zhang, Xu; Li, Shan; Lu, Xiangyun; Zhao, Chunyan; Yu, Qile; Wei, Zhengkai; Yang, Yongjun; Liu, Qun; Yang, Zhengtao; Li, Jianhua; et al. (Frontiers in Immunology, 2018)
Neospora caninum is an intracellular protozoan parasite closely related to Toxoplasma gondii that mainly infects canids as the definitive host and cattle as the intermediate host, resulting in abortion in cattle and leading to financial losses worldwide. Commercial vaccines or drugs are not available for the prevention and treatment of bovine neosporosis. Knowledge about the hallmarks of the immune response to this infection could form the basis of important prevention strategies. The innate immune system first responds to invading parasite and subsequently initiates the appropriate adaptive immune response against this parasite. Upon infection, activation of host pattern recognition receptors expressed by immune cells triggers the innate immune response. Toll-like receptors, NOD-like receptors and C-type lectin receptors play key roles in recognizing protozoan parasite. Therefore, we aimed to explore the role of the NLRP3 inflammasome during the acute period of Neospora caninum infection. In vitro results showed that Neospora caninum infection of murine bone marrow-derived macrophages activated the NLRP3 inflammasome, accompanied by the release of IL-1β and IL-18, cleavage of caspase-1, and induction of cell death. K+ efflux induced by Neospora caninum infection participated in the activation of the inflammasome. Infection of mice deficient in NLRP3, ASC, and caspase-1/11 resulted in decreased production of IL-18 and reduced IFN-γ in serum. Elevated numbers of monocytes/macrophages and neutrophils were found at the initial infection site, but they failed to limit Neospora caninum replication. These findings suggest that the NLRP3 inflammasome is involved in the host response to Neospora caninum infection at the acute stage, and plays an important role in limiting parasite growth, and it may enhance Th1 response by inducing production of IFN-γ. These findings may help devise protocols for controlling neosporosis.